Genetic linkage map of cassava (Manihot esculenta Crantz) based on AFLP and SSR markers - S. Kunkeaw (2018)
To generate a genetic linkage map of cassava (Manihot esculenta Crantz), 58 F1 progenies from a cross between Rayong 90 (female) and Rayong 5 (male) were examined in amplification fragment length polymorphism (AFLP) and simple sequence repeat (SSR) analyses. A total of 469 polymorphic markers consisting of 378 AFLPs generated from 76 primer combinations and 91 SSRs were identified. These markers were analyzed using the JOINMAP® 3.0 package program to construct a genetic linkage map. A total of 33 linkage groups of a common map were constructed from 119 AFLPs and 18 SSRs, spanning 1095 cM with an average of 7.99 cM between markers. The genetic linkage map generated in this study will be useful for genetic studies in cassava particularly for the identification of genetic markers linked to traits of interest, although the complex cassava genome suggests that maybe a long term objective. © 2009 Blackwell Verlag GmbH.